2008
DOI: 10.1515/jpm.2008.077
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific charts for abdominal circumference in term and near-term Caucasian newborns

Abstract: Sex-specific references constructed for AC in term and near-term Caucasian newborns might be used, as other anthropometric parameters, in the assessment of nutritional status at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
1
15
2
Order By: Relevance
“…None of these studies excluded smokers or mothers with medical diseases, nor were the results stratified by maternal pregestational BMI, parity, age or height. The Danish neonates had higher mean birth AC values at 40 weeks of gestation than those reported from Spain and China; boys, +1.3 cm and +1.1 cm; girls, +1.4 cm and +1.2 cm, respectively. In Swedish term neonates, mean AC values were 2.0 cm, and 1.5 cm higher, compared with our values for 40 weeks of gestation, boys and girls, respectively .…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…None of these studies excluded smokers or mothers with medical diseases, nor were the results stratified by maternal pregestational BMI, parity, age or height. The Danish neonates had higher mean birth AC values at 40 weeks of gestation than those reported from Spain and China; boys, +1.3 cm and +1.1 cm; girls, +1.4 cm and +1.2 cm, respectively. In Swedish term neonates, mean AC values were 2.0 cm, and 1.5 cm higher, compared with our values for 40 weeks of gestation, boys and girls, respectively .…”
Section: Discussioncontrasting
confidence: 58%
“…To our knowledge, the impact of maternal BMI on birth abdominal size has never been investigated on a population level. However, birth AC reference values have previously been reported based on small studies . None of these studies excluded smokers or mothers with medical diseases, nor were the results stratified by maternal pregestational BMI, parity, age or height.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study compared AC to gastric residuals to measure FI and suggested that AC use may be associated with a shorter time to full enteral feeding (11). AC reference values, however, are not available in very premature infants (12). Furthermore, the relationship between an increase in AC and the visual appearance of abdominal distention has never been studied.…”
Section: Introductionmentioning
confidence: 99%